Students' Perception on the Implementation of Literature Circle Activities in Extensive Reading Class - Itirna Itirna; Daniel Ari Widhiatama (Yayasan Karinosseff Muda Indonesia, 2023)
This research aimed to find out the studentsâ€™ perception on the implementation of Literature Circle in ER class. The design of this research was qualitative design research. This research was designed based on the problems identified and arranged to adjust the main purpose of the research so that the researcher employed a descriptive method. The researcher took 10 students as the sample of this research. The instruments of this study were observation and questionnaire. The researcher used questionnaire forms consisted of fifteen numbers of questions included in aspects of perception. Another instrument was an observation rubric.Â The findings of this research were; (1) the principles of ER have not been fully implemented in the Extensive reading class (2) Student's Perception of the implementation of the literature circle activity in ER Class has good benefits for students such as high interest and motivation in Extensive reading; (a) cognitive aspects, the Literature circle helps the Students to improve their reading skills and give them the freedom to choose books for pleasure, 77,8 %; (b) Literature Circle is an effective approach for the Extensive Reading class,55,6 %; (d) affective aspects increased student engagement, the utilization of Literature Circle methods fostered greater student involvement in the learning process,77,8 % , and conative aspects implementing the Literature Circle strategy actively involves students in reading while fostering their independence. Literature Circles serve as a cooperative learning tool that encourages students to take ownership of their reading choices and promote autonomy in engaging with personally selected texts, 66,7 %. Â